Comparing Methods to Assess Intraobserver Measurement Error of 3D Craniofacial Landmarks Using Geometric Morphometrics Through a Digitizer Arm - Menendez, Lumila Paula (2017)
Intraobserver error (INTRA-OE) is the difference between repeated measurements of the same variable made by the same observer. The objective of this work was to evaluate INTRA-OE from 3D landmarks registered with a Microscribe, in different datasets: (A) the 3D coordinates, (B) linear measurements calculated from A, and (C) the six-first principal component axes. INTRA-OE was analyzed by digitizing 42 landmarks from 23 skulls in three events two weeks apart from each other. Systematic error was tested through repeated measures ANOVA (ANOVA-RM), while random error through intraclass correlation coefficient. Results showed that the largest differences between the three observations were found in the first dataset. Some anatomical points like nasion, ectoconchion, temporosphenoparietal, asterion, and temporomandibular presented the highest INTRA-OE. In the second dataset, local distances had higher INTRA-OE than global distances while the third dataset showed the lowest INTRA-OE.